A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n. - Beccacece, Hernan Mario (Zootaxa, 2017)
A new species of Bertholdia Schaus is described: Bertholdia zoenia sp. n., based on males and females from Argentina and Paraguay. This new species is closer to Bertholdia myosticta Hampson, 1901 from Costa Rica, Irazú. Bertholdia zoenia sp. n. can be recognized externally because its hyaline spot on forewing is the widest among all species of genus. Also, the shape of this hyaline spot is like a right triangle with smooth outer margin, different from other species of genus, which have an irregular spot. Habitus, male and female genitalia, and particular structures of B. zoenia sp. n. are illustrated. Habitus and male genitalia of B. myosticta are also illustrated. A distribution map and commentaries of habitat of B. zoenia sp. n. and B. myosticta are given. Remarks on nomenclature of the genus are provided.